New Vaccines for Mammalian Allergy Using Molecular Approaches - van Hage, Marianne; Pauli, Gabrielle (Frontiers in Immunology, 2014)
Allergen-specific immunotherapy (SIT) offers a disease specific causative treatment by inducing tolerance to the allergen and preventing progression of allergic diseases. It may be considered in patients allergic to furry animals. Current mammalian allergy vaccines are still prepared from relatively poorly defined allergen extracts and may induce immediate and late phase side effects. Although the mechanisms of SIT are still not fully understood, the more recent approaches report different strategies to reduce both allergen-specific IgE as well as T cell reactivity. The availability of recombinant allergens and synthetic peptides from mammalian species has contributed to formulating new allergy vaccines to improve SIT for furry animal allergy. The majority of studies have focused on the major cat allergen Fel d 1 due to it’s extensively characterization in terms of IgE and T-cell epitopes and to its dominant role in cat allergy. Here we review the most recent approaches, e.g. synthetic peptides, recombinant allergen derivatives, different hypoallergenic molecules, recombinant allergens coupled to virus-like particles or immunomodulatory substances as well as strategies targeting the allergen to Fc receptors and the MHC class II pathway using a new route for administration. Many of the new vaccines hold promise but only a few of them have been investigated in clinical trials which will be the gold standard for evaluation of safety and efficacy in allergic patients.